Benign Focal Epilepsy of Childhood and Gastroesophagael Reflux - Anne G Sheehan; Sherry Pelensky; Colin Van Orman; Steven R Martin (Canadian Journal of Gastroenterology)
Gastroesophageal reflux has been associated with, and implicated in, a number of conditions, including respiratory disease (recurrent pneumonia, chronic cough, asthma), sudden infant death syndrome, dysphagia and central nervous disorders. An eight-year-old girl presented with an acute history that suggested gastroesophageal reflux. An esophageal motility study was abnormal and 24 h pH study demonstrated gastroesophageal reflux. Before the manometric study, a seizure was observed and subsequent neurological evaluation confirmed the diagnosis of benign focal epilepsy of childhood, which was treated with carbamazepine. The symptoms resolved after eight weeks and the repeat reflux investigations were essentially normal. Oropharyngeal symptoms are common in benign focal epilepsy of childhood, a condition which is very responsive to therapy. Symptoms suggestive of this diagnosis - acute onset, with unusual oropharyngeal sensations, or seizures-occurring mainly at night may initially be confused with gastroesophageal reflux. Benign focal epilepsy of childhood should be considered in reflux presenting outside infancy.